The therapist's notebook for children and adolescents : homework, handouts, and activities for use in psychotherapy - Sori, Catherine Ford; Hecker, Lorna; Bachenberg, Molli E. (New York : Routledge/Taylor & Francis Group, 2016)
'In The Therapist's Notebook for Children and Adolescents, 2nd ed, you'll find the most powerful tools available for aiding children with their feelings, incorporating play techniques into therapy, providing group therapy to children, and encouraging appropriate parental involvement. The new edition includes scores of new exercises and handouts on bullying, suicidal ideation, ADHD, autism, adolescents and sex, and cultural issues. It's a must-have arsenal for both novice and experienced professionals in family therapy, play therapy, psychology, psychiatry, counseling, education, nursing, and related fields'--
Includes bibliographical references and index.
Keywords: Mental disorders -- Therapy; Adolescent; Child; Psychotherapy -- methods; Handbooks